Durable and easy to clean laminate flooring

By using modified wear-resistant glue solution and end-hydroxyfluorosilic grafts in composite wood floors, combined with hot pressing technology, the poor toughness and stain resistance of the wear-resistant layer of composite wood floors are solved, and the durable and easy-to-clean reinforcement is achieved Laminate wood flooring.

CN115805743BActive Publication Date: 2024-12-27LAIAN YANGZI FLOORING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211517235.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-29
Publication Date
2024-12-27
Estimated Expiration
2042-11-29

AI Technical Summary

Technical Problem

The wear-resistant layer of existing composite wood floors has poor toughness, insufficient impact resistance, and poor stain resistance. It is difficult to clean after the surface is stained, making it impossible to achieve the purpose of durability and easy cleaning.

Method used

Using a modified wear-resistant glue solution, the wear-resistant decorative layer and balance layer are prepared by adding modified wear-resistant particles and end-hydroxyfluorosilic grafts to the wear-resistant glue solution, combined with a curing agent and melamine formaldehyde resin, and then the wear-resistant decorative layer is prepared and heated. The pressing process makes laminated wood flooring to improve its wear resistance, durability and easy cleaning.

Benefits of technology

Improve the wear resistance and durability of composite wood floors, enhance the hydrophobicity of the surface, reduce the wear rate and microcrack generation, achieve high wear resistance, high durability and easy cleaning effects, while reducing odor and environmental protection. risk.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003970733490000101
    Figure BDA0003970733490000101
Patent Text Reader

Abstract

The invention discloses a durable and easy-to-clean laminate composite wood floor, which belongs to the technical field of wood floor preparation. The durable and easy-to-clean laminate composite wood floor is provided with a wear-resistant decorative layer, a substrate layer and a balancing layer from top to bottom, and the preparation steps are as follows: adding a curing agent to a wear-resistant glue solution, immersing wood grain paper twice, controlling the amount of glue impregnation to 160-180%, pre-curing, and obtaining the wear-resistant decorative paper; adding a curing agent to a melamine formaldehyde resin, immersing the balancing base paper, controlling the amount of glue impregnation to 100-120%, pre-curing, and obtaining the impregnated balancing paper; and pressing the substrate, the impregnated balancing paper and the wear-resistant decorative paper into shape by a hot press to obtain the durable and easy-to-clean laminate composite wood floor. The invention introduces modified wear-resistant particles and terminal hydroxyl fluorosilicon grafts into the wear-resistant glue solution, so as to give the composite wood floor excellent wear resistance, antifouling and low volatility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wood floor preparation, and in particular relates to a durable and easy-to-clean laminate composite wood floor. Background Art

[0002] Composite wood flooring, also known as impregnated paper laminate wood flooring and laminate flooring, is generally composed of four layers of materials, namely, wear-resistant layer, decorative layer, high-density base material layer, and balance (moisture-proof) layer.

[0003] The wear-resistant layer of the existing composite wood floor is generally obtained by coating melamine formaldehyde resin with wear-resistant paper. The wear-resistant paper is mostly imported products with high cost, and the composite process of the wear-resistant layer and other layers is cumbersome. At present, research is conducted to use a "wet wear-resistant layer" to replace the wear-resistant paper, so as to ensure wear resistance while saving costs. The glue used in the existing wet wear-resistant layer is usually obtained by directly adding wear-resistant particles to the melamine formaldehyde resin solution. Due to the difference in polarity, the compatibility of the wear-resistant particles and the glue is poor. In addition, since melamine formaldehyde resin itself has the disadvantages of high hardness and fragility, the wear-resistant layer has poor toughness and poor mechanical properties such as impact resistance, and the purpose of improving durability cannot be achieved. Combined with the poor stain resistance of existing composite wood floors and the problem that the surface is difficult to clean after being stained, it is necessary to provide a durable and easy-to-clean laminate flooring. Summary of the invention

[0004] The object of the present invention is to provide a durable and easy-to-clean laminate flooring to solve the problems in the background technology.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] Durable and easy-to-clean laminate flooring is provided with a wear-resistant decorative layer, a substrate layer and a balancing layer from top to bottom, and is made by the following steps:

[0007] The first step is to add curing agent to the wear-resistant adhesive, and then add 70g / m 2 The wood grain paper is evenly dipped twice, and the amount of glue is controlled to be 160-180%. When no glue drips, it is immediately placed in an oven at 85°C and dried for 240 seconds to obtain wear-resistant decorative paper.

[0008] Step 2: Add curing agent to melamine formaldehyde resin, stir evenly and add 85g / m 2 The balanced base paper is immersed, and the amount of the impregnation is controlled to be 100-120%. When no more glue is dripped, it is immediately placed in an oven at 85°C and dried for 240 seconds to obtain the impregnated balanced paper;

[0009] The third step is to fix the hot pressing template on the upper pressing table of the hot press machine, fix the balancing paper hot pressing template on the lower pressing table of the hot press machine, place the substrate on the impregnated balancing paper, and send it to the hot press with a hot pressing temperature of 180-200℃, close the hot press, apply a pressure of 3-8MPs, maintain the pressure for 3-5s and then release the pressure, lay the wear-resistant decorative paper on the blank surface of the substrate (the other side of the impregnated balancing paper), control the temperature of 180-200℃, the pressure of 3-8MPa, maintain the pressure for 25-40s and then release the pressure, take out the board, and after segmentation and grooving, you can get a durable and easy-to-clean laminate flooring.

[0010] The substrate is a high-density fiberboard or particleboard, the mass ratio of the wear-resistant adhesive to the curing agent is 100:5-6, the mass ratio of the melamine formaldehyde resin to the curing agent is 100:5-6, and the solid content of the melamine formaldehyde resin is 52-55%.

[0011] Furthermore, the curing agent is one or more of ureaphthalic acid, triethanolamine and hexamethylenetetramine mixed in any proportion.

[0012] Further, the wear-resistant adhesive is prepared by the following steps:

[0013] Step a, under nitrogen protection, add tridecafluorooctanol, epoxy-terminated polydimethylsiloxane and DMF into a flask, heat to 40-50°C, stir for 5-8 minutes, add triethylamine, stir, heat to 130-150°C, stir and react for 3-5 hours, after the reaction is completed, remove the solvent by vacuum distillation to obtain a hydroxy-terminated fluorosilicon grafted product;

[0014] The dosage ratio of tridecafluorooctanol, epoxy-terminated polydimethylsiloxane, DMF and triethylamine is 7.4-11.2 g: 3.6-5.5 g: 100 mL: 1.5-2.1 g. Under the action of triethylamine, tridecafluorooctanol and epoxy-terminated polydimethylsiloxane undergo a ring-opening reaction to produce new hydroxyl groups, thereby obtaining a hydroxyl-terminated fluorosilicon grafted product.

[0015] Step b, adding dimethylacetamide to the reactor, adjusting the pH to 9-10 with a 20% sodium methoxide solution, stirring for 5 minutes, adding melamine and paraformaldehyde, stirring and reacting at 95° C. for 40 minutes, adding p-toluenesulfonic acid and terminal hydroxyl fluorosilicon grafted material, stirring and reacting at 90-95° C. for 40-60 minutes, cooling to 75-80° C., adding modified wear-resistant particles, keeping warm and reacting for 25-30 minutes, and after the reaction, adjusting the pH to 8.0 with triethylamine to obtain a wear-resistant rubber solution;

[0016] Among them, the dosage ratio of dimethylacetamide, melamine, polyformaldehyde and modified wear-resistant particles is 100mL: 0.3mol: 18g: 8-10g, the dosage of terminal hydroxyl fluorosilicone grafted material is 5-10% of the mass of melamine, the dosage of p-toluenesulfonic acid is 2% of the mass of terminal hydroxyl fluorosilicone grafted material, melamine and polyformaldehyde are used as raw materials to first carry out hydroxylation reaction, then graft the fluorosilicone grafted material through etherification reaction, and the modified wear-resistant particles are added to continue the reaction to obtain a wear-resistant rubber solution.

[0017] Further, the modified wear-resistant particles are prepared by the following steps:

[0018] Step A, mixing nano-spherical alumina, KH-560, anhydrous ethanol and deionized water evenly, stirring and reacting at 70° C. for 6-8 hours, filtering with suction, drying and transferring to a three-necked flask, adding a DMF solution of graphene oxide and triethylamine under nitrogen protection, stirring and reacting at 100° C. for 8-10 hours, filtering with suction after completion of the reaction, washing and drying the filter cake to obtain wear-resistant particles;

[0019] The amount ratio of nano-spherical alumina, KH-560, anhydrous ethanol, deionized water, graphene oxide and DMF is 2.5-3.0 g: 0.15-0.18 g: 30-40 mL: 10-15 mL: 5.5-6.4 g: 100 mL, the amount of triethylamine is 3-4% of the mass of the nano-spherical alumina and the acidified carbon fiber, and the DMF solution of graphene oxide is obtained by ultrasonically mixing graphene oxide and DMF;

[0020] Step B, adding wear-resistant particles, EDC and HOBt into a flask, stirring for 2 hours, then adding DMF solution of amino-terminated hyperbranched polyamide, reacting at room temperature for 4-5 hours, filtering after the reaction, rinsing with deionized water, and drying to obtain modified wear-resistant particles;

[0021] Among them, the usage ratio of wear-resistant particles, EDC (carbodiimide), HOBt (1-hydroxybenzotriazole) and amino-terminated hyperbranched polyamide DMF solution is 5g:0.56g:0.44g:100mL, and the amino-terminated hyperbranched polyamide DMF solution is composed of amino-terminated hyperbranched polyamide and DMF according to 0.25g:100mL.

[0022] Beneficial effects of the present invention:

[0023] 1. The laminate flooring of the present invention has strong wear resistance, mainly because the present invention introduces modified wear-resistant particles into the wear-resistant adhesive solution. The modified wear-resistant particles are hybrid particles chemically linked by graphene oxide and nano-alumina, and are obtained by modifying terminal amino hyperbranched polyamide. When added to the adhesive solution, the hyperbranched polyamide has a highly branched three-dimensional structure and a large molecular weight. Adding it to the matrix will not affect the bonding performance, and the dispersibility of the wear-resistant particles in the adhesive solution is improved. When the adhesive solution is cured to obtain a surface layer subjected to friction, the graphite oxide will be ground into graphite powder to form a graphite transfer film, which reduces the adhesion of the material to the friction surface during the friction process, thereby reducing the wear rate. Alumina, as a nanoparticle, is filled into a tiny space that the graphene oxide sheet cannot reach, thereby improving the overall strength of the surface layer, and has a nano "ball effect" during the friction process of the matrix, which plays a friction-reducing role.

[0024] 2. The durability of the laminated composite wood flooring of the present invention is high. Firstly, the wear resistance of the composite wood flooring is improved by adding modified wear-resistant particles. Secondly, terminal hydroxyl fluorosilicone grafts are introduced into the wear-resistant rubber of the present invention. The terminal hydroxyl fluorosilicone grafts can participate in the etherification reaction of melamine and polyformaldehyde, and introduce Si-O-Si long chains and FC long chains into the rubber. The Si-O-Si long chains are flexible polymer long chains with high bond energy. Introducing them into the glue can improve the toughness and high temperature resistance of the coating. Combined with the introduction of modified wear-resistant particles, when the material is impacted by external force, the wear-resistant particles can disperse the performance, consume energy, and inhibit the generation of microcracks, thereby giving the composite wood flooring higher durability.

[0025] 3. The laminated composite wood flooring of the present invention is easy to clean, because terminal hydroxyl fluorosilicone grafted substances are introduced into the glue, that is, Si-O-Si long chains and FC long chains are introduced, both of which have low surface characteristics, and the FC long chains have "skin-tending" properties, which can improve the hydrophobicity and oleophobicity of the surface of the laminated composite wood flooring, that is, improve the stain resistance.

[0026] 4. The laminated composite wood flooring of the present invention has low odor. The hyperbranched polyamide on the surface of the modified wear-resistant particles has a highly branched three-dimensional structure. The terminal amino group reacts with free formaldehyde to reduce the generation of volatile organic compounds, which is healthy and environmentally friendly. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] In the following examples, the epoxy-terminated polydimethylsiloxane is a commercial product produced by Gelest Company, with a molecular weight of 363-550 and an epoxy equivalent weight of 180-275 (g / eq); the amino-terminated hyperbranched polyamide is a commercial product purchased from Wuhan Hyperbranched Polyester Co., Ltd., with a brand name of HyPer N103 and an amino number of 12-16 / mol.

[0029] Example 1

[0030] This embodiment provides a modified wear-resistant particle, which is prepared by the following steps:

[0031] Step A, 2.5g of nano-spherical alumina, 0.15g of KH-560, 30mL of anhydrous ethanol and 10mL of deionized water were mixed evenly, stirred at 70°C for 6h, filtered, dried and transferred to a three-necked flask, and under nitrogen protection, 100mL of DMF solution containing 5.5g of graphene oxide and triethylamine were added, stirred at 100°C for 8h, and after the reaction was completed, filtered, the filter cake was washed and dried to obtain wear-resistant particles, and the amount of triethylamine was 3% of the mass of the nano-spherical alumina and the acidified carbon fiber;

[0032] Step B: Add 5 g of wear-resistant particles, 0.56 g of EDC and 0.44 g of HOBt into a flask, stir for 2 h, then add 100 mL of DMF solution containing 0.25 g of amino-terminated hyperbranched polyamide, react at room temperature for 4 h. After the reaction is completed, filter, rinse with deionized water, and dry to obtain modified wear-resistant particles.

[0033] Example 2

[0034] The modified wear-resistant particles are prepared by the following steps:

[0035] Step A, 3.0g of nano spherical alumina, 0.18g of KH-560, 40mL of anhydrous ethanol and 15mL of deionized water were mixed evenly, stirred at 70°C for 8h, filtered, dried and transferred to a three-necked flask, and under nitrogen protection, 100mL of DMF solution containing 6.4g of graphene oxide and triethylamine were added, stirred at 100°C for 10h, and after the reaction was completed, filtered, the filter cake was washed and dried to obtain wear-resistant particles, and the amount of triethylamine used was 4% of the mass of nano spherical alumina and acidified carbon fiber;

[0036] Step B: Add 5 g of wear-resistant particles, 0.56 g of EDC and 0.44 g of HOBt into a flask, stir for 2 h, then add 100 mL of DMF solution containing 0.25 g of amino-terminated hyperbranched polyamide, react at room temperature for 5 h, filter after the reaction, rinse with deionized water, and dry to obtain modified wear-resistant particles.

[0037] Comparative Example 1

[0038] This comparative example is the wear-resistant particles obtained in step A of Example 2.

[0039] Example 3

[0040] This embodiment provides a wear-resistant adhesive liquid, which is prepared by the following steps:

[0041] Step a, under nitrogen protection, add 7.4g of tridecafluorooctanol, 3.6g of terminal epoxy polydimethylsiloxane and 100mL of DMF into a flask, heat to 40°C, stir for 5min, add 1.5g of triethylamine, stir and heat to 130°C, stir and react for 3h, after the reaction is completed, remove the solvent by vacuum distillation to obtain a terminal hydroxyl fluorosilicon grafted product;

[0042] Step b, add 100mL of dimethylacetamide to the reactor, adjust the pH to 9 with a 20% mass fraction of sodium methoxide solution, stir for 5 minutes, add 0.3mol of melamine and 18g of paraformaldehyde, stir and react at 95°C for 40 minutes, add p-toluenesulfonic acid and terminal hydroxyl fluorosilicon grafts, stir and react at 90°C for 40 minutes, cool to 75°C, add 8g of the modified wear-resistant particles of Example 1, keep warm and react for 25 minutes, after the reaction is completed, adjust the pH to 8.0 with triethylamine to obtain a wear-resistant glue, the amount of terminal hydroxyl fluorosilicon grafts is 5% of the mass of melamine, and the amount of p-toluenesulfonic acid is 2% of the mass of the terminal hydroxyl fluorosilicon grafts.

[0043] Example 4

[0044] This embodiment provides a wear-resistant adhesive liquid, which is prepared by the following steps:

[0045] Step a, under nitrogen protection, add 11.2g of tridecafluorooctanol, 5.5g of epoxy-terminated polydimethylsiloxane and 100mL of DMF into a flask, heat to 50°C, stir for 8min, add 2.1g of triethylamine, stir and heat to 150°C, stir and react for 5h, after the reaction is completed, remove the solvent by vacuum distillation to obtain a hydroxy-terminated fluorosilicon grafted product;

[0046] Step b, add 100mL of dimethylacetamide to the reactor, adjust the pH to 10 with a 20% mass fraction of sodium methoxide solution, stir for 5 minutes, add 0.3mol of melamine and 18g of paraformaldehyde, stir and react at 95°C for 40 minutes, add p-toluenesulfonic acid and terminal hydroxyl fluorosilicon grafts, stir and react at 95°C for 60 minutes, cool to 80°C, add 10g of the modified wear-resistant particles of Example 2, and keep warm for 30 minutes. After the reaction, adjust the pH to 8.0 with triethylamine to obtain a wear-resistant glue, the amount of terminal hydroxyl fluorosilicon grafts is 10% of the mass of melamine, and the amount of p-toluenesulfonic acid is 2% of the mass of the terminal hydroxyl fluorosilicon grafts.

[0047] Comparative Example 2

[0048] Compared with Example 3, the modified wear-resistant particles in Example 3 are replaced by the material in Comparative Example 1, and the remaining raw materials and preparation process are the same as in Example 3.

[0049] Comparative Example 3

[0050] Compared with Example 4, the terminal hydroxyl fluorosilicon grafted material in Example 4 is removed, and the remaining raw materials and preparation process are the same as Example 4.

[0051] Example 5

[0052] Durable and easy-to-clean laminate flooring is provided with a wear-resistant decorative layer, a substrate layer and a balancing layer from top to bottom, and is made by the following steps:

[0053] The first step is to add triethanolamine to the wear-resistant adhesive of Example 3, the mass ratio of the wear-resistant adhesive to triethanolamine is 100:5, and then add 70g / m 2 The wood grain paper is evenly dipped twice, and the amount of glue is controlled to be 160%. When no glue drips, it is immediately placed in an oven at 85°C and dried for 240 seconds to obtain wear-resistant decorative paper.

[0054] Step 2: Add triethanolamine to the melamine formaldehyde resin. The mass ratio of melamine formaldehyde resin to triethanolamine is 100:5. The solid content of melamine formaldehyde resin is 52%. After stirring evenly, 85g / m 2 The balanced base paper is immersed in the glue, and the amount of the impregnation is controlled to be 100%. When no glue drips, it is immediately placed in an oven at 85°C for drying for 240 seconds to obtain the impregnated balanced paper;

[0055] The third step is to fix the hot pressing template on the upper pressing table of the hot press machine, fix the balancing paper hot pressing template on the lower pressing table of the hot press machine, place the high-density fiberboard on the impregnated balancing paper, and send it to the hot press with a hot pressing temperature of 180°C. Close the hot press, apply a pressure of 3MPs, maintain the pressure for 5s and then release the pressure, lay the wear-resistant decorative paper on the blank surface of the substrate (the other side of the impregnated balancing paper), control 180°C, pressure of 3MPa, maintain the pressure for 40s and then release the pressure, take out the board, and after splitting, grooving and tenoning, you can get a durable and easy-to-clean laminate flooring.

[0056] Example 6

[0057] Durable and easy-to-clean laminate flooring is provided with a wear-resistant decorative layer, a substrate layer and a balancing layer from top to bottom, and is made by the following steps:

[0058] The first step is to add urea phthalic acid to the wear-resistant adhesive of Example 4, the mass ratio of the wear-resistant adhesive to urea phthalic acid is 100:5, and then add 70g / m 2The wood grain paper is evenly dipped twice, and the amount of glue is controlled to be 170%. When no glue drips, it is immediately placed in an oven at 85°C and dried for 240 seconds to obtain wear-resistant decorative paper.

[0059] Step 2: Add urea phthalic acid to the melamine formaldehyde resin. The mass ratio of melamine formaldehyde resin to urea phthalic acid is 100:5. The solid content of melamine formaldehyde resin is 54%. After stirring evenly, 85 g / m 2 The balanced base paper is immersed in the glue, and the amount of the impregnation is controlled to be 110%. When no glue drips, it is immediately placed in an oven at 85°C and dried for 240 seconds to obtain the impregnated balanced paper;

[0060] The third step is to fix the hot pressing template on the upper pressing table of the hot press machine, fix the balancing paper hot pressing template on the lower pressing table of the hot press machine, place the particleboard on the impregnated balancing paper, and send it to the hot press with a hot pressing temperature of 190℃. Close the hot press, apply a pressure of 5MPs, maintain the pressure for 4s and then release the pressure. Lay the wear-resistant decorative paper on the blank surface of the substrate (the other side of the impregnated balancing paper), control 190℃, pressure of 5MPa, maintain the pressure for 35s and then release the pressure. Take out the board, and after splitting, grooving and tenoning, you can get a durable and easy-to-clean laminate flooring.

[0061] Example 7

[0062] Durable and easy-to-clean laminate flooring is provided with a wear-resistant decorative layer, a substrate layer and a balancing layer from top to bottom, and is made by the following steps:

[0063] The first step is to add hexamethylenetetramine to the wear-resistant adhesive of Example 4, the mass ratio of the wear-resistant adhesive to hexamethylenetetramine is 100:6, and then add 70g / m 2 The wood grain paper is evenly dipped twice, and the amount of glue is controlled to be 180%. When no glue drips, it is immediately placed in an oven at 85°C and dried for 240 seconds to obtain wear-resistant decorative paper.

[0064] Step 2: Add hexamethylenetetramine to the melamine formaldehyde resin. The mass ratio of melamine formaldehyde resin to hexamethylenetetramine is 100:6. The solid content of melamine formaldehyde resin is 55%. After stirring evenly, 85 g / m 2 The balanced base paper is immersed in the glue, and the amount of the impregnation is controlled to be 120%. When no glue drips, it is immediately placed in an oven at 85°C and dried for 240 seconds to obtain the impregnated balanced paper;

[0065] The third step is to fix the hot pressing template on the upper pressing table of the hot press, fix the balancing paper hot pressing template on the lower pressing table of the hot press, place the particleboard on the impregnated balancing paper, send it into the hot press with a hot pressing temperature of 200℃, close the hot press, apply a pressure of 8MPs, maintain the pressure for 5s and then release the pressure, lay the wear-resistant decorative paper on the blank surface of the substrate (the other side of the impregnated balancing paper), control the temperature at 200℃ and the pressure at 8MPa, maintain the pressure for 40s and then release the pressure, take out the board, and after splitting and grooving, you can get a durable and easy-to-clean laminate flooring.

[0066] Comparative Example 4

[0067] Compared with Example 5, the wear-resistant rubber liquid in Example 5 is replaced by the substance in Comparative Example 2, and the remaining raw materials and preparation process are the same as in Example 5.

[0068] Comparative Example 5

[0069] Compared with Example 5, the wear-resistant rubber liquid in Example 5 is replaced by the substance in Comparative Example 3, and the remaining raw materials and preparation process are the same as in Example 5.

[0070] The performance of the laminated composite wood flooring obtained in Examples 5-7 and Comparative Examples 4-5 was tested, and the test items were as follows:

[0071] Cleanability: (1) Surface contact angle: test the contact angle of the wear-resistant decorative layer according to the operating procedures of the static drop contact angle / interfacial tension measuring instrument JC2000A; (2) Oil resistance: take 0.2g of shoe polish, apply it on the wear-resistant decorative layer with a dry rag, and ensure that at least 50×20mm of the area is completely covered. Wipe it clean with a wet rag dipped in soapy water, then wipe it dry with a dry rag, observe the phenomenon and record it;

[0072] Wear resistance: Treat the specimen according to the method specified in 6.3 of the national standard GB / T 18102-2007 "Impregnated paper laminated wood flooring", fix the wear-resistant decorative layer on the TABER abrasion tester, install the grinding wheel on the bracket, and record the damaged area of ​​the specimen to be no less than 0.6mm 2 Wear revolutions;

[0073] Environmental protection: Refer to standard GB18580-2001 to test formaldehyde emission;

[0074] The test results are shown in Table 1:

[0075] Table 1

[0076]

[0077]

[0078] It can be seen from Table 1 that, compared with Comparative Examples 4-5, the composite wood flooring prepared in Examples 5-7 has high wear resistance, is easy to clean, and has low formaldehyde volatilization;

[0079] By comparing Comparative Example 4 with Example 5, it can be seen that the introduction of modified wear-resistant particles has a greater impact on the wear resistance and formaldehyde emission of the composite wood floor. The reason is that the modified wear-resistant particles can be evenly dispersed in the rubber, and the aluminum oxide, as nanoparticles, is filled into the tiny space that the graphene oxide sheet cannot reach, thereby improving the overall wear resistance of the surface layer, and the terminal amino group reacts with free formaldehyde to reduce the generation of volatile organic matter;

[0080] By comparing Comparative Example 5 with Example 5, it can be seen that the introduction of the terminal hydroxyl fluorosilicone graft has a greater effect on the cleaning performance and surface contact angle of the composite wood floor. The reason is that the addition of the terminal hydroxyl fluorosilicone graft introduces Si-O-Si long chains and FC long chains into the rubber material, both of which have low surface properties, and the FC long chain has a "skin-tending" property, which can improve the hydrophobicity and oleophobicity of the surface of the laminate composite wood floor, that is, improve the stain resistance;

[0081] In summary, the composite wood floor prepared by the present invention is highly durable and easy to clean.

[0082] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0083] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. Durable and easy-to-clean laminate flooring, which is provided with a wear-resistant decorative layer, a substrate layer and a balancing layer from top to bottom, characterized in that: The method comprises the following steps: The first step is to add dimethylacetamide to the reactor, adjust the pH to 9-10 with 20wt% sodium methoxide solution, add melamine and paraformaldehyde after stirring, add p-toluenesulfonic acid and terminal hydroxyl fluorosilicon grafted product after stirring at 95°C, react at 90-95°C with stirring for 40-60min, cool to 75-80°C, add modified wear-resistant particles, keep warm for 25-30min, adjust the pH to 8.0, and obtain wear-resistant glue; Step 2: Add curing agent to the wear-resistant glue solution, immerse the wood grain paper twice, control the dipping amount to 160-180%, pre-cure, and obtain wear-resistant decorative paper; The third step is to add a curing agent to the melamine formaldehyde resin, immerse the balanced base paper, control the dipping amount to 100-120%, pre-cure, and obtain the impregnated balanced paper; Step 4: Press the substrate, the impregnated balancing paper and the wear-resistant decorative paper into shape using a hot press to obtain a durable and easy-to-clean laminate flooring; The hydroxy-terminated fluorosilicone grafted compound is prepared by the following steps: Under nitrogen protection, tridecafluorooctanol, epoxy-terminated polydimethylsiloxane and DMF were mixed, stirred at 40-50°C for 5-8 minutes, triethylamine was added, the temperature was raised to 130-150°C, and the reaction was stirred for 3-5 hours to obtain a hydroxy-terminated fluorosilicone grafted product; The modified wear-resistant particles are prepared by the following steps: Step A, mixing nano-spherical alumina, KH-560, anhydrous ethanol and deionized water, stirring and reacting at 70° C. for 6-8 hours, filtering, drying and transferring to a three-necked flask, adding a DMF solution of graphene oxide and triethylamine under nitrogen protection, stirring and reacting at 100° C. for 8-10 hours, and obtaining wear-resistant particles; Step B: Mix the wear-resistant particles, EDC and HOBt, stir for 2 hours, add the DMF solution of the amino-terminated hyperbranched polyamide, and react at room temperature for 4-5 hours to obtain modified wear-resistant particles.

2. The durable and easy-to-clean laminate flooring according to claim 1, characterized in that: Pre-curing refers to drying in an oven at 85°C for 240 seconds, with the mass ratio of wear-resistant adhesive to curing agent being 100:5-6.

3. The durable and easy-to-clean laminate flooring according to claim 1, characterized in that: The dosage ratio of dimethylacetamide, melamine, polyformaldehyde and modified wear-resistant particles is 100mL: 0.3mol: 18g: 8-10g, the dosage of terminal hydroxyl fluorosilicone grafted material is 5-10% of the mass of melamine, and the dosage of p-toluenesulfonic acid is 2% of the mass of terminal hydroxyl fluorosilicone grafted material.

4. The durable and easy-to-clean laminate flooring according to claim 1, characterized in that: The usage ratio of tridecafluorooctanol, epoxy-terminated polydimethylsiloxane, DMF and triethylamine is 7.4-11.2 g: 3.6-5.5 g: 100 mL: 1.5-2.1 g.

5. The durable and easy-to-clean laminate flooring according to claim 1, characterized in that: The amino-terminated hyperbranched polyamide DMF solution is composed of the amino-terminated hyperbranched polyamide and DMF in a ratio of 0.25 g:100 mL.